Qur’anic Exegesis in the Digital Age: An Analysis of the Hegemony of Social Media–Based Tafsir in Shaping Millennials’ Islamic Understanding - Waro, Mochamad Tholib Khoiril (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2024)
In the digital era, social media has become a dominant platform for the dissemination of Qur'anic interpretation, especially among the millennial generation. This article aims to analyze how social media hegemony shapes this generation's understanding of Islam. Through a descriptive qualitative approach, this study explores the forms of hegemony that emerge from various interpretations of the Qur'an on social media, including their impact on traditional religious authorities. The results of the study show that social media promotes greater accessibility, but it also has the potential to reduce the quality and depth of understanding of Islam.